Clinical Information Systems Integration in New York City's First Mobile Stroke Unit - Kummer, Benjamin R.; Lerario, Michael P.; Navi, Babak B.; Ganzman, Adam C.; Ribaudo, Daniel; Mir, Saad A.; Pishanidar, Sammy; Lekic, Tim; Williams, Olajide; Kamel, Hooman; Marshall, Randolph S.; Hripcsak, George; Elkind, Mitchell S.V.; Fink, Matthew E. (Applied Clinical Informatics, 2018)
Background Mobile stroke units (MSUs) reduce time to thrombolytic therapy in acute ischemic stroke. These units are widely used, but the clinical information systems underlying MSU operations are understudied.Objective The first MSU on the East Coast of the United States was established at New York Presbyterian Hospital (NYP) in October 2016. We describe our program's 7-month pilot, focusing on the integration of our hospital's clinical information systems into our MSU to support patient care and research efforts.Methods NYP's MSU was staffed by two paramedics, one radiology technologist, and a vascular neurologist. The unit was equipped with four laptop computers and networking infrastructure enabling all staff to access the hospital intranet and clinical applications during operating hours. A telephone-based registration procedure registered patients from the field into our admit/discharge/transfer system, which interfaced with the institutional electronic health record (EHR). We developed and implemented a computerized physician order entry set in our EHR with prefilled values to permit quick ordering of medications, imaging, and laboratory testing. We also developed and implemented a structured clinician note to facilitate care documentation and clinical data extraction.Results Our MSU began operating on October 3, 2016. As of April 27, 2017, the MSU transported 49 patients, of whom 16 received tissue plasminogen activator (t-PA). Zero technical problems impacting patient care were reported around registration, order entry, or intranet access. Two onboard network failures occurred, resulting in computed tomography scanner malfunctions, although no patients became ineligible for time-sensitive treatment as a result. Thirteen (26.5%) clinical notes contained at least one incomplete time field.Conclusion The main technical challenges encountered during the integration of our hospital's clinical information systems into our MSU were onboard network failures and incomplete clinical documentation. Future studies are necessary to determine whether such integrative efforts improve MSU care quality, and which enhancements to information systems will optimize clinical care and research efforts.
Keywords: stroke; mobile health units; integrated information systems; implementation and deployment; use, administration, and maintenance; electronic health records and systems; order entry; radiology information systems; clinical documentation and communications